Contratación pública sostenible: entre el derecho europeo y el nuevo código italiano (Tema Central) - Cozzio, Michele (2025)
The choice to enter the sustainable development market is a common process that connects countries with different economic, cultural, and traditional lifestyles from East to West, albeit with varying outcomes. The European Union has integrated sustainability goals into its policies, strategies, and rules concerning public procurement. In this context, the Italian model is characterized by the innovative value of solutions adopted for green and socially sustainable contracts, directions now also favored by EU legislators. The principle of do no significant harm (DNSH) is among the most promising tools for developing public contracts in support of decarbonization goals and, more broadly, the green transition. All these innovations depict an evolution in the European public procurement system, where its initial economic connotation plays an instrumental role in achieving the objectives of the European social pillar and ecological transition.